2017
DOI: 10.1080/14767058.2017.1406915
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal outcomes related to iron supplementation or iron status: a summary of meta-analyses

Abstract: Our summary of meta-analyses showed that multimicronutrient supplementation had beneficial effects on some neonatal outcomes. Furthermore, higher ferritin levels seem to increase the risk for GDM whereas maternal anemia was associated with adverse birth/neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 48 publications
2
34
1
3
Order By: Relevance
“…Even after the adjustment for several reasonable confounding factors, such impact was still existed. Our result was consistent with several previous epidemiological studies that have reported an association between body iron status and GDM [6,7,15,16]. They found that high maternal hemoglobin level and/or high serum ferritin levels were the risk factor for GDM [15].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Even after the adjustment for several reasonable confounding factors, such impact was still existed. Our result was consistent with several previous epidemiological studies that have reported an association between body iron status and GDM [6,7,15,16]. They found that high maternal hemoglobin level and/or high serum ferritin levels were the risk factor for GDM [15].…”
Section: Discussionsupporting
confidence: 93%
“…There were some studies showing that pregnant women without antenatal iron supplement had adverse obstetric outcomes including maternal anemia, preterm delivery and low birth weight infant [11,16,19]. However, in the present study, the early (before 16 weeks gestation) and the later (after 16 weeks gestation) iron supplementation had comparable infants' birth weight, length of gestational period, and incidence of maternal anemia at delivery.…”
Section: Discussioncontrasting
confidence: 69%
“…Various other factors that could have effects on the HbA1c and GDM such as or ferritin, iron levels, and hepcidin were not assessed in our study 36,37 . We failed to follow‐up these women so as to access the maternal and perinatal outcomes in relation to HbA1c.…”
Section: Resultsmentioning
confidence: 99%
“…Fe deficiency is a common cause of anaemia, and daily Fe supplementation may result in an increase in Hb values in 11 % of pregnant women ( 32 ) . A recent meta-analysis indicated that both Fe deficiency and Fe excess would increase the risk of gestational disease and pregnancy outcomes ( 33 ) . In China, free prenatal Fe supplements were not provided by the government.…”
Section: Discussionmentioning
confidence: 99%